RANCANGAN ALGORITMA GENERATOR MODEL 3D UNTUK MEMBUAT OBJEK BERUPA CABAI - Sukoco, Omega Rimba Gemilang, M. Suyanto (Jurnal Ilmiah SINUS, 2017)
Abstract Along later development of technology, 3D models are increasingly used almost in all circles and fields. With so a 3D model can be used as a medium of learning simulations and attractive arranged in such a way. Alongside the presence of 3D applications that can be used both free and proprietary, animators develop Karyana expected to support the learning of interest. Â The aim of this study as a learning medium and can be used as a computer program to create 3D models. In accordance with the proper sequence of steps, the process of making the object will be greatly facilitated. And supported by using a script program is expected to create objects in large quantities can be easily and vary in shape and size but they can be modified by the animator. Generator 3D model is a solution to create objects in large quantities. 3D models created as an instance is the object of the chili. Generator 3D model has been tested and is capable of forming a desired object. Â Keywordsâ€” Algorithm, Python, Modeling, 3D Models, Generator